‘AIR QUALITY’ IN REGULATIONS OF THE REPUBLIC OF SERBIA AND THE EUROPEAN UNION (FROM AN AMBIGUOUS DEFINITION TO A COMPLEX AIR PROTECTION SYSTEM) - Todić, Dragoljub C; Дујић, Иван (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
The introductory part of the paper highlights the importance of ‘air quality’ and provides methodological clarifications. The second part of the paper compares some elements of the legal systems of the Republic of Serbia (RS) and the European Union (EU) in the field of air protection (existence of strategic documents in the field of air protection, legal framework, legal definition of the term ‘air quality’, prescribing pollutants that threaten ‘air quality’, prescribing the competencies of respective authorities and bodies in the field of air protection, setting up zones and agglomerations, monitoring ‘air quality’, informing the public about ‘air quality’, and status in relevant treaties relating to air quality). The main objective of the paper is to identify the places that ‘air quality’ occupies in the legal system of RS, and the EU respectively, as well as to analyse the level of compliance of RS internal regulations with the relevant EU regulations. In conclusion, it is stated that a significant part of the rules deriving directly from the Air Quality Directive 2008/50/EC has been transposed into the internal regulations of RS. However, a part of the rules has just to be transposed. It is also noted that the law does not clearly define what exactly the term ‘air quality’ means, although the term occupies a significant place in RS and the EU regulations. The content of this term should be interpreted in the context of the air protection system as a whole.
Keywords: ‘air quality’; air protection; environment; pollutants; Directive 2008/50/EC; RS regulations; regulatory compliance; international treaties